Efek Anti Fungi Ekstrak Etanol Kulit Buah Manggis (Garcinia Mangostana, Linn.) Terhadap Pertumbuhan Candida Albicans Secara In Vitro - ., Puspaningrum; Sukilarso S, FX.Bambang; Wijayanti, Lilik (Nexus Biomedika, 2013)
Background: This study aimed to know the inhibitory effect of the etanol extract of mangosteen rind (Garcinia mangostana, Linn.) on the growth of Candida albicans in vitro. Methods: The method used in this study was quasi-experimental laboratory research. The subject was the ethanol extract of the mangosteen fruit (Garcinia mangostana Linn.) rind. Candida albicans grown on sabouraud dextrose agar were treated with 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% of the ethanol extract of mangosteen rind (Garcinia mangostana, Linn.), as well as fluconazole 25Î¼g (drugs that were already on the market) as positive control for 24 hours at 37Â° C on petri dish. The data of diameter of inhibition zone obtained were analyzed with regression-correlation test using SPSS 11.5 for windows. Results: The diameters of inhibition zone on culture of Candida albicans treated with the ethanol extract of the mangosteen fruit with concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, and fluconazole 25Î¼g were 0 mm, 0 mm, 1.75 mm, 1.75 mm, 2.00 mm, 2.00 mm, 3.00 mm, 3.50 mm, 3.75 mm, 3.75 mm and 0 mm, in a row. The regression-correlation analysis showed that the correlation (r) between the diameter of inhibition zone and the levels of ethanol extract of mangosteen rind was 0.936 (p 0.000). Conclusion: The ethanol extract of mangosteen rind (Garcinia mangostana, Linn.) had antifungal effect on the growth of Candida albicans in vitro. Keywords: antifungal effects, ethanol extract of mangosteen rind (Garcinia mangostana Linn.), Candida albicans. Â